Twenty-six new species of Hoploscopa (Lepidoptera, Crambidae) from South-East Asia revealed by morphology and DNA barcoding - Théo Léger (ZooKeys, 2020)
Hoploscopa are mid-sized reddish-brown moths with white, yellow or red pattern elements which inhabit montane wet forests of South-East Asia, from Thailand to the Samoan Islands. With only sixteen species described - all, with one exception, were described between the end of 19th and beginning of 20th century - the diversity of this genus was exceedingly under estimated. Previous authors suggested the occurrence of at least 70 species in the British Museum (NHM, London) awaiting description. A recent paper brought the first host plant records on ferns for this genus and provided COI barcodes for some undescribed species. Examination of morphology and COI barcodes from museum specimens and collected material as well as of the type specimens of hitherto described species led to the description of 26 new species, bringing the total number of species in the genus to 41. Interestingly, these moths show a high degree of endemism: the few species ranging over several islands show pronounced barcode splits (2 to 5 %) between islands, raising questions about species boundaries among island populations. Another thirty species still described are estimated from the collection of the NMH London and will be the scope of a second publication.